1978
DOI: 10.1029/jb083ib06p02839
|View full text |Cite
|
Sign up to set email alerts
|

Compression wave studies on calcite rock

Abstract: Dynamic compression wave studies have been conducted on three calcite rocks, Solenhofen limestone, Oakhall limestone, and Vermont marble, in the stress range of 0–5 GPa. Plate impact techniques provided transient stress wave input, and diffuse laser interferometry was used to study the evolution of these pulses through various thicknesses of rock. Both loading response and release wave response were determined from the time‐resolved particle velocity profiles. The calcite I–II and II–III phase transitions dram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
51
1

Year Published

1984
1984
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(62 citation statements)
references
References 24 publications
10
51
1
Order By: Relevance
“…The recent literature on this subject is now extensive; one may refer to [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19], [34,35] and their associated references. The resulting mechanical response replicates material behavior as observed in a host of important materials including crystalline solids [20,21], shape memory alloys [22], polymers and rubber [23]. It has been suggested that this theory may describe the mechanical behavior associated with elastic-plastic material response and with the pseudo-elastic shape memory effect [15,16].…”
Section: Introductionmentioning
confidence: 97%
“…The recent literature on this subject is now extensive; one may refer to [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19], [34,35] and their associated references. The resulting mechanical response replicates material behavior as observed in a host of important materials including crystalline solids [20,21], shape memory alloys [22], polymers and rubber [23]. It has been suggested that this theory may describe the mechanical behavior associated with elastic-plastic material response and with the pseudo-elastic shape memory effect [15,16].…”
Section: Introductionmentioning
confidence: 97%
“…10 is applicable at high pressure even when calcite (high-pressure phase) is completely transformed to CaO and CO 2 , i.e., K becomes 1. Previous shock wave measurements reported that calcite undergoes three phase transitions: calcite I to II transition between 0.6 and 1.2 GPa, calcite II to III transition around 2.4 GPa, and III to IV transition around 10 GPa [20,29]. We have used the isentrope of phase IV as the reference state.…”
Section: Temperature Calculation With Disproportionation Of Calcite (mentioning
confidence: 99%
“…The problem is introduced in section II, where it is reviewed how change of phase phenomena can be modelled by means of a nonmonotonic stress-strain law. These laws have been studied previously in [1], [2], [3]; a relevant experimental study is (4].…”
Section: And Phase Boundaries In Elastic Barsmentioning
confidence: 99%
“…The separated strain intervals are now associated with different material phases. Here the value of the transition stress a is assumed to be a property of the material (see [4] S"The condition (2.4) indicates that the bar is taken to be initially undeformed and at rest. The condition (2.3) can also be written…”
Section: (C)mentioning
confidence: 99%